DIGITAL MATURITY AS A FACTOR OF STRATEGIC MANAGEMENT EFFECTIVENESS IN ORGANIZATIONS - S.Q. Saydalieva (Ta’lim innovatsiyasi va integratsiyasi, 2026)
Abstract This article examines digital maturity as a determinant of strategic management effectiveness, focusing on project-oriented organizations navigating digital transformation. Drawing on comparative analysis, qualitative organizational assessment, and synthesis of contemporary literature, the study maps six core maturity dimensions-data and analytics, process automation, technology integration, organizational culture, strategic leadership, and customer engagement-against a spectrum of management outcomes. Organizations at low maturity levels exhibit a characteristic cluster of dysfunctions: fragmented digitalization, manual coordination dependency, weak analytical infrastructure, communication overload, and limited scalability-conditions that directly erode strategic coherence. A phased development framework is proposed, comprising process formalization, centralized project management, CRM integration, KPI-based monitoring, business intelligence adoption, and digital capability building. The findings contribute to digital strategy literature and offer actionable guidance for practitioners in emerging market contexts.